Motivations, institutional perceptions and venture performance of women entrepreneurs in South Africa - Manilal, Avani (My University, 2019)
This study was initiated to explore the relatively low entrepreneurial participation rates of women as well as the sustainability of their enterprises, which may be regarded as entrepreneurial outcomes or performance. The literature revealed that both individual factors and contextual factors may have an influence on entrepreneurial performance. The purpose of this research was to establish how women entrepreneurs' motivations and their perceptions of institutions influence venture performance, with a focus on SMEs in the formal sector in Gauteng province, South Africa. The targeted respondents for this study were women entrepreneurs who own 51 % or more of small to medium-sized enterprises based in Gauteng, where the maximum annual turnover of their businesses was not more than R64 million. Empirical analysis including exploratory factor analysis and multiple regression analysis was conducted to understand the relationships between entrepreneurial motivations and institutional perceptions with venture performance as an outcome. It was established that entrepreneurial motivations, represented by a single factor, 'general motivations', was not a significant predictor of venture performance. The institutional profile revealed that the regulatory and cognitive institutions were perceived to be less favourable than the normative dimension. Cognitive institutions were found to have a positive influence on venture performance, whereas regulatory and normative institutions were not significant contributors. Lastly, it was found that perceptions of regulatory, normative and cognitive institutions did not moderate the effect of entrepreneurial motivations on venture performance. The findings have important implications in terms of entrepreneurial policy as well as development and support for women entrepreneurs in a South African context.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand, 2019